2012
DOI: 10.1371/journal.pone.0045559
|View full text |Cite
|
Sign up to set email alerts
|

Decorin Protein Core Affects the Global Gene Expression Profile of the Tumor Microenvironment in a Triple-Negative Orthotopic Breast Carcinoma Xenograft Model

Abstract: Decorin, a member of the small leucine-rich proteoglycan gene family, exists and functions wholly within the tumor microenvironment to suppress tumorigenesis by directly targeting and antagonizing multiple receptor tyrosine kinases, such as the EGFR and Met. This leads to potent and sustained signal attenuation, growth arrest, and angiostasis. We thus sought to evaluate the tumoricidal benefits of systemic decorin on a triple-negative orthotopic breast carcinoma xenograft model. To this end, we employed a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
106
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 111 publications
0
106
1
Order By: Relevance
“…The first line of evidence to tie decorin signaling to Peg3 came from the empirical demonstration of Peg3 induction exclusively within the tumor microenvironment following systemic administration of decorin (24). Immunofluorescence studies revealed a dramatic association of Peg3 with subcellular structures resembling autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first line of evidence to tie decorin signaling to Peg3 came from the empirical demonstration of Peg3 induction exclusively within the tumor microenvironment following systemic administration of decorin (24). Immunofluorescence studies revealed a dramatic association of Peg3 with subcellular structures resembling autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Specificity was confirmed by the lack of an autophagic response in the presence of equimolar amounts of biglycan protein core, the closest molecular relative of decorin. Decorin, by signaling via RTK interactions, can ameliorate the overall antitumor properties of the tumor stroma by counteracting malignant development to stymie tumor progression (5,13,24) and angiogenesis (20,23). Typically, these interactions are exclusively antagonistic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DCN transfection elevated the phosphorylation level of TGF-βRI in HepG2 cells, without affecting the total TGF-βRI expression. The p15 protein is one of the key downstream factors of TGF-βRI, whose activation may influence cell cycle-associated proteins, further inhibiting the cell proliferation [8]. The current results showed that DCN transfection was able to significantly elevate the expression level of p15.…”
Section: Discussionmentioning
confidence: 48%